Pollen contamination and mating structure in maritime pine (Pinus pinaster Ait.) clonal seed orchards revealed by SNP markers - Bouffier, Laurent; Debille, Sandrine; Alazard, Pierre; Raffin, Annie; Pastuszka, Patrick; Trontin, Jean-François (Peer Community Journal)

(untitled)
Maritime pine (Pinus pinaster Ait.) is a major forest tree species in south-western Europe. In France, an advanced breeding program for this conifer species has been underway since the early 1960s. Open-pollinated seed orchards currently supply more than 90% of maritime pine seedlings for plantation forestry. However, pollen contamination and mating structure have been poorly studied in such seed orchards whereas they could impact genetic gains and diversity. We analyzed these features in three maritime pine clonal seed orchards. We addressed biological (tree genotype, age, flowering phenology) and environmental factors (vicinity with external pollen sources, orchard structure, soil type, climatic conditions) that are expected to determine the genetic composition of seed lots. Genetic analyses were based on an optimized set of 60 SNP markers and performed on 2,552 seedlings with Cervus software (likelihood inference methodology). Pollen contamination rates were highly variable between seed lots (from 20 to 96%), with a mean value of 50%. Interpretative factors included the distance between the seed orchard and external pollen sources, rain during the pollination period, seed orchard age, soil conditions and seed parent identity. All parental genotypes from the seed orchards contributed to the offspring as pollen parents, but differences in paternal reproductive success were detected. Finally, the overall self-fertilization rate was estimated at 5.4%, with considerable variability between genotypes (from 0% to 26%). These findings are useful to formulate recommendations for seed orchard management (seed orchard location, soil and climate optimal conditions, minimum age for commercial seed lots harvesting) and for identifying new research perspectives (exploring links between pollen contamination and climatic data, genetic control of flowering traits).